EKSISTENSI DAYAH DI ACEH MASA KOLONIALISME SAMPAI ORDE BARU (1900-1998) - Basri Basri (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2022)
Dayah has existed as one of the education centers and contributed to integrating all aspects at a very significant level in Aceh towards education and politics. In earlier the 20 century, the development of Dayah was supervised by the Dutch government. Nevertheless, Dayah still presented its authority through the idea, pattern, curriculum, and method of dynamic learning. As a result, it played a role as a good model to create Islamic tradition, learning community, and charismatic Islamic scholars. In general, they will transform their responsibility not only as a religious scholar but also as a statesman who dedicates themselves to political change in Aceh.